Perspektiver inden for teknologisk-assisteret indsamling af data i psykologisk forandring – rammesat af den synergetiske psykologi. - Lyby, Marlene Skovgaard; Mehlsen, Mimi Yung (Psyke & Logos, 2016)
It is a methodological challenge to describe change processes within psychology, as change is often characterized by both loss and growth in function. Especially compensatory processes may be impossible to describe by conventional methods. These methods typically detect changes in the level of functionality from one point to another, but are unable to identify the processes that mediate the development. A micro-genetic method that is based on high-frequency data collection, may be suitable to describe change processes in normative populations, as well as psychopathological. As data density is greater and the observed processes of change can be non-linear, registration, analyzes, and interpretation of microgenetic data do, however, challenge the conventional methods of measurement in psychological research. Within the framework of Synergetics (a theory of self-organization in complex dynamical systems), Günter Schiepek and colleagues have developed a tool for registration and analysis: the Synergetic Navigation System. This system enables closemonitoring of clients’ mental state during critical development phases and offers support for therapeutic processes. In both cases, clients’ dynamic development processes exhibit characteristics that can be described and analyzed using concepts and methods from Synergetics. This publication describes how the approach can be applied in research in adult development of emotion regulation and how it may be useful in a clinical setting.